A Diagnostic Rarity: Apocrine Hidrocystoma Presenting as a Medial Canthal Mass in Adolescence - Atika Syafendra; Mardijas Efendi; Ardizal Rahman (HM Publisher, 2025)
Background: Apocrine hidrocystomas are benign adnexal tumors of the glands of Moll, typically diagnosed in adults. Their presentation in adolescence is an exceptional clinical finding that challenges standard diagnostic paradigms for periocular masses in this age group, necessitating a broad and meticulous differential diagnosis. Case presentation: A 15-year-old female presented with a two-month history of a stable, asymptomatic, 7×5×1 mm cystic mass at the inferomedial canthus of the left eye. The patient's primary concern was cosmetic. A comprehensive ophthalmologic examination was unremarkable. Orbital computed tomography confirmed a simple, preseptal subcutaneous cyst. A complete excisional biopsy was performed, and histopathological analysis revealed a unilocular cyst lined by a double layer of epithelium with inner columnar cells demonstrating pathognomonic decapitation secretion, confirming an apocrine hidrocystoma. Conclusion: This case highlights the necessity of including apocrine hidrocystoma in the differential diagnosis of periocular masses in adolescents. The primary lesson is that a patient's age should broaden, not narrow, the diagnostic possibilities. Definitive diagnosis relies on histopathology, not demographic probability, and complete surgical excision remains the gold standard for both diagnosis and curative therapy, yielding an excellent prognosis.